Match-play running activity in elite female soccer field and assistant referees - Carling, C.; Doudet, F.; Gruson, B.; Prat, J.-M.; Pavillon, T. (Biology of Sport, 2025)
This study aimed to 1) describe running outputs during official match-play in elite French female Field (FR) and Assistant Referees (AR), 2) determine whether decrements in outputs occurred in the 2nd-half and during the final 15-minute interval of each half. A total of 13 elite female game officials participated: 6 AR (age: 28.9 ± 5.1) and 7 FR (age: 28.1 ± 2.0). Outputs were collected using GPS over 3 consecutive seasons (2020/21-2022/23). Competitions included elite senior female/male domestic matches and international female/male youth & senior matches (n = 501; AR = 285, FR = 216). Variables included: total distance covered (km), distances travelled (m) at low- (< 13 km/h) and high-speeds (>= 13 km/h, >= 19 km/h, >= 23 km/h) and the frequency of high-intensity acceleration & deceleration events (>= 3 m·s -2). Mean outputs per minute were compared across match halves and for the first 15-minute versus the final 15-minute interval in each half using Effect Sizes (ES). Main results showed that FR covered approximately 9.5 km per game of which 24% was at high-speeds (D >= 13 km/h) while AR travelled ~5 km (~14% ran at high-speeds). More high-intensity deceleration versus acceleration events were observed for both roles. Outputs generally dropped in the 2nd versus the 1st half (FR = small to moderate and AR = small to large ES) and during the final 15-minute intervals in each half versus the first 15-minutes in the 1st-half (FR = moderate to large and AR = small to large ES). This study has established general match running activity profiles for elite French assistant and field referees and reported a trend for a temporal decline in outputs whilst demonstrating the importance of performing deceleration events.